중·장년층의 사회적 고립이 우울과 위험 음주에 미치는 영향: 종단적 상호인과관계 검증 - 석소원(So-Won Suk) (한국콘텐츠학회 논문지, 24(11), 2024)
본 연구는 중·장년층의 우울 및 위험 음주의 시간적 발달 단계의 종단적 변화 양상과 사회적 고립이 우울 및 위험 음주에 미치는 영향을 확인하여 중·장년층의 삶의 질 향상을 위한 개입 방안을 모색하는 것을 목적으로 하였다. 분석을 위해 한국노동연구원의 고령화연구 패널조사에서 중·장년층을 대상으로 7차부터 9차까지의 기간에 걸쳐 구축한 자료 중 865명을 대상으로 자기회귀교차지연모형 검증을 실시하였다. 연구 결과는 다음과 같다. 첫째, 중·장년층의 사회적 고립이 우울에 직접적 영향을 미치는 것으로 나타났다. 둘째, 중·장년층의 우울과 위험 음주는 시간의 흐름에 따라 강한 자기회귀 효과를 보였다. 셋째, 중·장년층의 우울과 위험 음주는 시간이 흐르면서 서로 영향을 주고받는 상호교류적 관계임이 확인되었으며, 이는 중·장년층의 우울과 위험 음주가 서로 악순환을 형성하며, 정신건강 문제를 악화시키는 중요한 요인이 되는 것으로 나타났다. 본 연구는 중·장년층의 우울, 위험 음주가 상호 순환적 관계이며 사회적 고립이 우울 증상과 위험 음주의 종단적 상호인과관계에 영향을 미치는 경로가 다르며, 이에 대한 실천 현장의 개입이 다르게 이루어져야 함을 확인하였다는 데에 의의가 있다. This study aimed to explore intervention strategies for improving the quality of life of middle-aged adults by examining the longitudinal changes in depression and risky drinking and the impact of social isolation on these variables. For the analysis, an autoregressive cross-lagged model (ARCL) was tested using data from 865 participants, collected over the 7th to 9th waves of the Korean Longitudinal Study of Aging (KLoSA) conducted by the Korea Labor Institute, targeting the middle-aged and older population. The findings were as follows. First, social isolation had a direct impact on depression in middle-aged adults. Second, depression and risky drinking among middle-aged and elderly people showed a strong autoregressive effect over time. Third, it was found that depression and risky drinking among middle-aged and elderly people were mutually influenced other over time, which showed that depression and risky drinking among middle-aged and elderly people formed a vicious cycle and were important factors in exacerbating mental health problems. This study highlighted the cyclical relationship between depression and risky drinking in middle-aged adults and revealed that the pathways through which social isolation affected depression and risky drinking were different. The study emphasizes the importance of targeted interventions in addressing these mental health challenges in practice. KCI Citation Count: 0